السياسة التجريمية في الشريعة الإسلامية والقانون الوضعي - شوية, موسى (University of eloued جامعة الوادي, 2016)
This thesis treats an important subject of the fiqh of criminality, which consists on the criminalization policy in both of Islamic law and the positive law, which is considered as an important element of criminal policy that aims to protect human interests from any assault or damage. Throughout this thesis I tried to collect the right elements to answer the questions asked in this research. For this sake it is necessary to identify each of the criminalization policy and the policy of criminalization, the definition in both Sharia and positive law, and by definition I moved to disperse separately; in language and terminology. The overall definition of criminal policy is centered on: the fight against criminality and crime prevention to preserve the public interests. In the other side criminalization policy is to protect and preserve the interests, by banning and criminalizing all damage that may harm; by removing some acts from the acceptable into prohibition. Then I moved to the theoretical basis of the criminalization policy; determining the philosophy of criminality in Sharia; and that is based on determining the criminal responsibility of individuals, as well as the law; ; in which his philosophy in criminalization was based on a set of theories that knew developments and successive stages. This incriminating policy has also characterized by several properties; whether the gradation of legislation in Sharia, and putting the general rules and the abstract laws, as well as relativity, objectivity and its strategies and evolution. This is what we talk about in the first chapter of this study. In the second chapter; it was specified to talk about the criminalization policy and related provisions. So I talked first about the sources of criminality; whether they are relate to Sharia or to the positive law. Then he moved on to talk about the classification of crimes in Sharia and the positive law, where it is classified by Islamic law to Hodoud (punishments) and crimes, and crimes of retaliation and compromise, and crimes Taazer (the threat of harder punishment), while the positive law has classified the crimes into felonies and misdemeanors and infractions. At the end of this study I focused on what should be taken into account in criminality in both Sharia and positive law; basing on the criminalization policy which relays on the principle of criminal legitimacy, as well as considering the protected interests from criminalization which is found for its sake and cannot succeed without it, in addition to some restrictions controls that limit criminalization and adherence of abuse and injustice. At the end of my thesis I conclude it with the results and findings that I achieved.
شريعة وقانون
Keywords: القانون/السياسة التجريمية/الشريعة الإسلامية; Law/Criminal Politics/Islamic Law